(untitled) (University of Khartoum Engineering Journal, 2022)
Wireless access has become an essential part of modern society. Consequently, new wireless applications and services, as well as the number of wireless users, are sharply increasing. Cognitive radio has improved the spectral efficiency of licensed radio frequency bands by accessing unused part of the band opportunistically without interfering with a licensed primary user. Spectrum mobility improves fast and smooth transition that lead to minimum performance degradation. An important requirement of mobility management protocols is a good performance in relation to spectrum handoff. To reduce the adverse effects of spectrum handoff interrupted secondary users may be provided with a higher priority over new secondary users for utilizing the available spectrum band. In this paper a queuing model of a spectrum handoff scheme for cognitive radio wireless networks is proposed. The handoff performance of the secondary users operating in a heterogeneous spectrum situation composed of licensed channels and unlicensed channels is tested., Three types of users: primary users, new secondary users, and handoff (Interrupted) secondary users are considered. The discrete event Simulator Matrix Laboratory (MATLAB) package tool is used to carry numerical calculations illustrating the effect of a priority queuing system on the performance of handoff of Secondary Users (SUs).